Badanie stopnia zadowolenia pacjentów z usług medycznych - Ucieklak-Jeż, Paulina (Measurement of Patient Satisfaction with Medical Health Care, 2007)
The measurement of patient satisfaction was performed in one of the integrated health care managements units, that is ZOZ in Częstochowa. The applied measurement instrument was PSQ-18 Questionnaire, which is the short-form version of the 50-item Patient Satisfaction Questionnaire III (PSQ-III). The PSQ-18 contains 18 items covering each of the 7 dimensions of patient satisfaction with the medical care: general satisfaction, technical quality, interpersonal manner, communication, financial aspects, time spent with doctor, accessibility and convenience. The factor analysis was used to find the factors influencing the patient satisfaction from medical care services. The results indicate that the majority of the patients was not satisfied with the medical health care in the considered unit, and women were less satisfied than men.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1163, s. 297-313